بدایات الفكر الجمھوري في العراق 1908 - 1921 دراسة تاريخية (Journal of the College of Education for Women, 2019)
The main target of this research is to follow the stages of the emergence ofthe idea of republican form of government from its very beginning , yet therewere many elements from different estates thinker , educated , few of heads ofclans . This first opportunity for the mobilization of politically-minded peoplewith fundamental activity like najei shokat . hussain al-rahal notable poet marufal-rasafi those who formed what so called the political elite who believed inconstitutional , democratic parliamentary republic , one of them was al-rahal whocalled for a constitutional republic even before the emergence of theconstitutional movement in Iran and ottoman empire (1908).The holy najaf become cultural center or conference attended by youngintellectuals , liberal and conservative and religious ideological and layman thusit become obvious that political theater of najaf contained all talentsThe Anglo-French declaration of which professed adherence to the wishesof the people under direct rule of them . This declaration that dated 7th October1918 lead to divide the Iraqi national movement in tow groups , monarchies andrepublican .The Cairo conference in which w. chirchill chairman of the politicalcommittee agreed upon Faysal as the most suitable ruler for Iraq . Sir percy coxclearly said . That complete consolation of the whishes of the inhibition by meansof representative assembly as to the nature of permanent government wasimpossible before setup the machinery of the future government he deem it asessential to initiate immediately some form of national government regardless ofthe unfavorable conditions .Talib al-naqib was the real rivals to Faysal after little later from his exile(cylon) in February 1920 become Avery active supporter the Britishadministration knowing that the britsh were searching for ruler for Iraq with hisposition as minister of the interior so he continued to press his candid . Philbyencouraged him to hope for British backing so it was a good pretax to arrest himand to get rid of Philby . so the idea of republic regime impaired .